The Effect of Sexual Abuse on Deviant Behaviors Among Turkish Adolescents: The Mediating Role of Emotions - Solakoglu, Ozgur (International journal of offender therapy and comparative criminology, 2018)
Drawing from Robert Agnew’s General Strain Theory, the purpose of this study is to examine the effect of sexual abuse on deviant behaviors, such as suicide, smoking, drinking, drug use, violent crime, and property crime, among Turkish adolescents. The article also aims to understand the mediating role of negative emotions, including depression and anger, as well as gender differences in this relationship. Findings from a series of analyses demonstrate that the experience of sexual abuse is significantly related to the likelihood of engaging in most of the deviant behaviors. In addition, the mediating role of negative emotions, particularly anger, was highlighted in the findings. Furthermore, the effect of sexual abuse on deviant behaviors was relatively greater for Turkish males compared with Turkish females. The current study contributes to the literature on the consequences of sexual abuse by considering them within the unique Islamic-Western cultural context of Turkey. Overall, findings suggest that this particular form of strain has a substantial impact on deviant behaviors among Turkish adolescents.